A Global Cypher: The Role of Hip Hop in Cultural Identity Construction and Navigation for Southeast Asian American Youth. Issue 164 (19th March 2019) - Nguyen, Jacqueline; Ferguson, Gail M.
Abstract: Southeast Asian American (SEAA) adolescents and emerging adults navigate a multicultural, global world by utilizing cultural variability to play up and play down three cultural identities: their Asian/Asian American heritage culture, the White dominant culture in which they live, and a hip hop cultural identity. The latter is a unique cultural identity rooted in the global phenomenon of hip hop that includes dance, art, and music as well as resistance to the dominant, mainstream culture. Hip hop is a meaningful cultural identity for SEAA youth because it is a cultural identity transcendent of race/ethnicity, a means toward relational and identity harmony, a form of resistance, and because it facilitates belongingness to a local and a global community.